Generation of data sets for semi-empirical models of circulated fluidized bed boilers using hybrid Euler-Lagrange technique. (15th January 2018) - Adamczyk, Wojciech P.; Myöhänen, Kari; Hartge, Ernst-Ulrich; Ritvanen, Jouni; Klimanek, Adam; Hyppänen, Timo; Białecki, Ryszard A.
Abstract: The primary goal when designing a CFB boiler is to ensure its high energy efficiency. Additional constraints come from environmental regulations, which are constantly becoming more difficult to assess, and require improvements in the boiler design process. Local on-site measurements are often restricted to short distances inward from the furnace wall, leaving most of the core unmeasured. Computer simulations are practically the only feasible tools to investigate the combustion processes and to support the design of CFB units. Three-dimensional steady-state semi-empirical CFB furnace models predict adequate results within reasonable times but these models require tuning to existing objects, which obviously excludes their application for new object design. The present study represents a step toward using the hybrid Euler–Lagrange (HEL) technique to model flow variables in order to replace the measured data. The information collected using the HEL model for an arbitrary furnace can be used to tune a semi-empirical model. To validate the HEL model, measurements of a 235 MWe CFB were used. The simulations show good agreement between the numerical and experimental results, indicating that the presented idea is worth investigating in the future. Highlights: Application of hybrid EL approach for modeling large scale CFB boiler. No-reacting and reacting case modeling. Development of hybrid EL model for efficient modeling large scale CFB boilers. Extensive comparison of numerical results with experimental data.